Small‐Molecule‐Based Organic Field‐Effect Transistor for Nonvolatile Memory and Artificial Synapse. (19th September 2019) - Yu, Yang; Ma, Qihao; Ling, Haifeng; Li, Wen; Ju, Ruolin; Bian, Linyi; Shi, Naien; Qian, Yan; Yi, Mingdong; Xie, Linghai; Huang, Wei
Abstract: With the incorporation of tailorable organic electronic materials as channel and storage materials, organic field‐effect transistor (OFET)‐based memory has become one of the most promising data storage technologies for hosting a variety of emerging memory applications, such as sensory memory, storage memory, and neuromorphic computing. Here, the recent state‐of‐the‐art progresses in the use of small molecules for OFET nonvolatile memory and artificial synapses are comprehensively reviewed, focusing on the characteristic features of small molecules in versatile functional roles (channel, storage, modifier, and dopant). Techniques for optimizing the storage capacity, speed, and reliability of nonvolatile memory devices are addressed in detail. Insight into the use of small molecules in artificial synapses constructed on OFET memory is also obtained in this emerging field. Finally, the strategies of molecular design for improving memory performance in view of small molecules as storage mediums are discussed systematically, and challenges are addressed to shed light on the future development of this vital research field. Abstract : Recent advances in small‐molecule‐based organic field‐effect transistors for nonvolatile memory and artificial synapse are comprehensively reviewed. Working mechanisms and optimization approaches are discussed in detail, with a view toward inspiring more intriguing ideas on the rational design of materials and device structures.